2016
DOI: 10.1093/jhps/hnw035
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of femoroacetabular impingement-current concepts

Abstract: Following the recognition of femoroacetabular impingement (FAI) as a clinical entity, diagnostic tools have continuously evolved. While the diagnosis of FAI is primarily made based on the patients’ history and clinical examination, imaging of FAI is indispensable. Routine diagnostic work-up consists of a set of plain radiographs, magnetic resonance imaging (MRI) and MR-arthrography. Recent advances in MRI technology include biochemically sensitive sequences bearing the potential to detect degenerative changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 147 publications
0
32
0
2
Order By: Relevance
“…Femoroacetabular impingement is a dynamic phenomenon that results from conflict between the proximal femur and the acetabular rim during hip motion [ 4 , 46 ]. It is caused by abnormal bony morphology, especially when the joint is subjected to exertional forces and a range of motion beyond normal physiological limits [ 4 , 46 ]. The bony abnormality may be at the femoral head-neck junction (cam morphology), acetabular rim (pincer morphology), or a combination of both (mixed).…”
Section: Intra-articular Pathologymentioning
confidence: 99%
“…Femoroacetabular impingement is a dynamic phenomenon that results from conflict between the proximal femur and the acetabular rim during hip motion [ 4 , 46 ]. It is caused by abnormal bony morphology, especially when the joint is subjected to exertional forces and a range of motion beyond normal physiological limits [ 4 , 46 ]. The bony abnormality may be at the femoral head-neck junction (cam morphology), acetabular rim (pincer morphology), or a combination of both (mixed).…”
Section: Intra-articular Pathologymentioning
confidence: 99%
“…Notzli et al showed a value above 50° is associated with cam lesion impingement in FAI 28. Femoral head–neck offset is another measurement used to define cam lesions and is the distance between a parallel line down the center of the femoral neck and a parallel line that passes through the point where the femoral head–neck contour exceeds the femoral head radius divided by the diameter of the femoral head 29. A ratio of less than 0.17 is suggestive of a cam deformity.…”
Section: Imagingmentioning
confidence: 99%
“…Labral lesions are common with FAI and are able to be evaluated with MRI/MRA (Figure 3A). Cartilage lesions are also common in FAI and can be seen and characterized by MRI/MRA, with a higher sensitivity of detection with MRA 29. Bony morphology of the acetabulum and femur can also be evaluated with MRI/MRA (Figure 3B).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Computed tomography (CT) scans provide the best contrast between bone and soft tissues and are amenable to three-dimensional reconstruction. 3 Threedimensional CT models provide excellent visualization and measurements of bony morphology independent of patient position in the CT scanner. Thus, CT scans are the best imaging modality for diagnosis of bony hip abnormalities.…”
mentioning
confidence: 99%